The jurisprudential and legal development of the rights and duties of the related parent: a look towards the fulfillment of the best interests of the child - Bazán Dobbertin, Ursula (2022)
This article is based on our recent research, in which we have analyzed how the normative vacuum in the regulation of the related parent affects the best interest of the child, since in Peru there are no express norms in this regard, thus violating various rights of children and adolescents. Although we have found some norms in which, isolated and tacitly, there is some kind of mention, this is not enough to guarantee the fulfillment of the best interest of the child.